2013
DOI: 10.1088/0031-9155/58/22/8179
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pulsed IMRT and VMAT for re-irradiation treatments: dosimetric and delivery feasibilities

Abstract: Many tumor cells demonstrate hyperradiosensitivity at doses below ~50 cGy. Together with the increased normal tissue repair under low dose rate, the pulsed low dose rate radiotherapy (PLDR), which separates a daily fractional dose of 200 cGy into 10 pulses with 3 min interval between pulses (~20 cGy/pulse and effective dose rate 6.7 cGy min−1), potentially reduces late normal tissue toxicity while still providing significant tumor control for re-irradiation treatments. This work investigates the dosimetric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The dosimetric quality and treatment delivery characteristics have been evaluated by previous investigators [59,1218] . Intrinsically, VMAT uses more beam angles and therefore spreads the incident/exit beams more evenly in surrounding normal tissues leading to more uniform surface doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosimetric quality and treatment delivery characteristics have been evaluated by previous investigators [59,1218] . Intrinsically, VMAT uses more beam angles and therefore spreads the incident/exit beams more evenly in surrounding normal tissues leading to more uniform surface doses.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, a systematic investigation of static field IMRT and single- and double-arc VMAT plans led to a clinical decision to allow for both IMRT (typically 7 to 9 fields) and VMAT with at least two arcs [12] . Lin et al demonstrated that VMAT (with two arcs) was more suitable for centrally located targets while IMRT was more advantageous for large, irregular-shaped or peripheral targets although accurate treatment delivery could be achieved with both modalities [18] . In a busy clinic with limited planning capabilities it would be impractical to perform comparisons of different treatment techniques (e.g., even between Arc1 and Arc2) for every patient.…”
Section: Discussionmentioning
confidence: 99%
“…Focal SBRT to the recurrent intraprostatic tumor (12) with internal organ immobilization (13) and rectal sparing (14), as well as combination of hyperthermia and RT (15) or delivery of pulsed low-dose-rate schedules (16), should be explored in very selected cases as alternative reirradiation modalities in accurately designed prospective trials.…”
Section: (8-17)mentioning
confidence: 99%
“…[1][2][3][4] This involves spreading out a conventional radiation therapy dose into short pulses of dose with breaks in between. By example, a PLDR regimen may involve delivering a dose of 2 Gy as 10 pulses of 0.2 Gy, each 3 minutes apart.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 While cell survival data from cell lines and in vivo animal experiments have been published, no mechanistic data are available to explain the phenomenon of improved clinical toxicity with this treatment technique. Therefore, we performed in vivo experiments in mice to investigate the effect of PLDR and conventional radiotherapy (CRT) on normal tissues.…”
Section: Introductionmentioning
confidence: 99%